The European Union and Education for Democratic Citizenship Legal foundations for EU learning at school - Grimonprez, Kris (Luxemburger Juristische Studien - Luxembourg Legal Studies, 2020)
The study makes an analysis of the legal framework which Member States must take into account when designing their policies on citizenship education. The Charter on Education for Democratic Citizenship and Human Rights Education of the Council of Europe and the international right to education are read in conjunction with EU law. Suitable content for the EU dimension in mainstream education is explored. A method for objective, critical and pluralistic EU learning is proposed, based on the Treaties and on case teaching (stories for critical thinking). Member States are invited to take more action to ensure quality education. The EU has the legal competence to support the EU dimension in education. In the present state of EU law, quality education is no longer conceivable without an EU dimension incorporated in various key competences. At present the author works at the implementation of the ideas developed in the book as an Affiliated Senior Researcher at Leuven University (Case4EU-project in Belgium and other EU Member States). Das Werk bringt die Europarats-Charta zur politischen Bildung zusammen mit dem EU-Recht. Es steckt den rechtlichen Gestaltungsrahmen der Mitgliedstaaten im Hinblick demokratische Bildung und Erziehung ab. Auf der Basis konkreter Methoden werden Maßnahmen vorgeschlagen, mit denen die Mitgliedstaaten eine qualitativ höherwertige demokratische Bildung sicherstellen können. Dies ist ohne eine genuin europäische Dimension in verschiedenen Schlüsselkompetenzen nicht mehr denkbar.